Analisis Peran Likuiditas dan Penerapan Prinsip-prinsip Good Corporate Governance dalam Meningkatkan Nilai Perusahaan (Literature Review) - Cici Pujiyanti; Mochamad Muhtadin; Rudi Sanjaya (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the role of liquidity and the implementation of Good Corporate Governance (GCG) principles in increasing company value. Using the literature review method, this study identifies the results of previous studies related to the relationship between liquidity, GCG implementation, and company value. The results of the literature show that good liquidity provides financial stability for the company, while the implementation of GCG principles, such as transparency, accountability, responsibility, independence, and fairness, can increase investor confidence. The synergy between optimal liquidity and effective GCG implementation has a significant impact on increasing company value.